Penerapan Konvergensi Media Dalam Komunikasi Pemasaran Untuk Memperkuat Citra Merek Voks Radio Bali 102 FM - Dewi, Ni Nyoman Cipta; Sutika, I Made; Prasyudyo (Kinesik, 2025)
The purpose of this article is to analyze the implementation of media convergence in the marketing communication strategy conducted by VOKS Radio Bali 102 FM and identify the challenges faced by VOKS Radio Bali 102 FM in implementing media convergence to strengthen brand image. This research uses qualitative descriptive method. The subjects in this study were employees of the program division and marketing promotion division of Voks Radio Bali 102 FM. The data analysis technique used in analyzing the data of this research is inductive technique by assessing the empirical facts found then matched with the basis of theoretical studies and existing indicators. The results showed that Voks Radio Bali 102 FM implemented Media Convergence by utilizing Mobile Applications, thus it had a significant impact on improving Brand Image. The obstacles faced in implementing Media Convergence are the equipment needed to produce content in various formats and the employees' capabilities that need to be improved.